Utilization of Comprehensive Mathematical Modelling to Evaluate the Growth Kinetics of Pseudomonas putida LY1 on Phenol - Aisami, Abubakar; Usman, Mohammed Maikudi (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Kinetic equations, which explain the behaviour of a microbe or an enzyme towards a specific substrate, are key to understanding many phenomena in biotechnological processes. They facilitate the mathematical prediction of growth parameters essential for the identification of key growth control parameters. We remodelled Banerjee and Ghoshal’s published research (Banerjee and Ghoshal 2010) using some more kinetic growth models, such as Monod, Teissier, Andrews and Noack, Hinshelwood, Moser, Aiba, Webb (Edward), Yano and Koga, Han and Levenspiel and Luong used statistical methods such as Root Mean Square (RMSE), Adjusted Coefficient of Determination ( R2), corrected Akaike Information Criterion (AICc), Bias Factor, Accuracy Factor to determine the accuracy of the fitted model. The best model was Haldane with the true value of ïmax determined as the value where the gradient for the slope is zero was 0.115 h-1 at 51 mg/L phenol. The results indicate that the exhaustive use of mathematical models on available published results could gleam new optimal models that can provide new knowledge on the way toxic substance inhibits growth rate in microbes.